ALAN is a computational approach that interprets genomic findings in the context of tumor ecosystems - Hannah E. Bergom; Ashraf Shabaneh; Abderrahman Day; Atef Ali; Ella Boytim; Sydney Tape; John R. Lozada; Xiaolei Shi; Carlos Perez Kerkvliet; Sean McSweeney; Samuel P. Pitzen; Megan Ludwig; et al. (Communications Biology, 2023)
Abstract Gene behavior is governed by activity of other genes in an ecosystem as well as context-specific cues including cell type, microenvironment, and prior exposure to therapy. Here, we developed the Algorithm for Linking Activity Networks (ALAN) to compare gene behavior purely based on patient -omic data. The types of gene behaviors identifiable by ALAN include co-regulators of a signaling pathway, protein-protein interactions, or any set of genes that function similarly. ALAN identified direct protein-protein interactions in prostate cancer (AR, HOXB13, and FOXA1). We found differential and complex ALAN networks associated with the proto-oncogene MYC as prostate tumors develop and become metastatic, between different cancer types, and within cancer subtypes. We discovered that resistant genes in prostate cancer shared an ALAN ecosystem and activated similar oncogenic signaling pathways. Altogether, ALAN represents an informatics approach for developing gene signatures, identifying gene targets, and interpreting mechanisms of progression or therapy resistance.